Primary angle closure glaucoma - Vargas-Gonzales, Enrique (2023)
Primary angle-closure glaucoma is an ocular pathology that, in its acute presentation, can significantly compromise the patient's visual capacity. The clinical presentation may present systemic symptoms such as headache, nausea and vomiting, similar to a migraine. For this reason, it is extremely important to identify those symptoms and signs that can guide us to recognize or suspect this pathology in order to establish an initial treatment and be able to refer it to a specialist in a timely manner.